Earlier plant growth helps compensate for reduced carbon fixation after 13 years of warming. (22nd August 2019) - Winkler, Daniel E.; Grossiord, Charlotte; Belnap, Jayne; Howell, Armin; Ferrenberg, Scott; Smith, Hilda; Reed, Sasha C.
Abstract: Drylands play a dominant role in global carbon cycling and are particularly vulnerable to increasing temperatures, but our understanding of how dryland ecosystems will respond to climatic change remains notably poor. Considering that the area of drylands is projected to increase by 11%–23% by 2, 100, understanding the impacts of warming on the functions and services furnished by these arid and semi‐arid ecosystems has numerous implications. In a unique 13‐year ecosystem warming experiment in a south‐western U.S. dryland, we investigated the consequences of rising temperature on Achnatherum hymenoides, a widespread, keystone grass species on the Colorado Plateau. We tracked individual‐ and population‐level responses to identify optimal strategies that may have been masked if considering only one level of plant response. We found several factors combined to affect the timing and magnitude of plant responses during the 13th year of warming. These included large warming‐induced biomass increases for individual plants, an 8.5‐day advancement in the growing season and strong reductions in photosynthetic rates and population cover. Importantly, we observed a lack of photosynthetic acclimation and, thus, a warming‐induced downregulation of photosynthetic rates. However, these physiological responses were concurrent with warmed‐plant increases in growing season length and investment in photosynthetic surfaces, demonstrating the species' ability to balance carbon fixation limitations with warming. These results, which bring together ecophysiological, phenological, reproductive and morphological assessments of plant responses to warming, suggest that the extent of change in A.  hymenoides populations will be based upon numerous adaptive responses that vary in their direction and magnitude. Plant population responses to climatic warming remain poorly resolved, particularly for Earth's drylands, and our in situ experiment assessing multiple strategies offers a novel look into a warmer world. A free Plain Language Summary can be found within the Supporting Information of this article. Abstract : A free Plain Language Summary can be found within the Supporting Information of this article.